2020
DOI: 10.3390/cancers12061679
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Biogenesis and Activities from the Perspective of Its Direct Interacting Partners

Abstract: Telomerase reverse transcriptase (TERT)—the catalytic subunit of telomerase—is reactivated in up to 90% of all human cancers. TERT is observed in heterogenous populations of protein complexes, which are dynamically regulated in a cell type- and cell cycle-specific manner. Over the past two decades, in vitro protein–protein interaction detection methods have discovered a number of endogenous TERT binding partners in human cells that are responsible for the biogenesis and functionalization of the telomerase holo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 118 publications
(165 reference statements)
0
13
0
Order By: Relevance
“…Telomerase activity is negatively regulated by the nucleolar protein PIN2/TERF1-interacting telomerase inhibitor 1 (PINX1) [171]. Nucleophosmin (NPM) and microspherule protein 2 (MCRS2) may be S phase-specific co-effectors of PINX1, working against each other to modulate the human TERT pool (reviewed in [172]). Telomerase is then recruited to Cajal bodies (CBs).…”
Section: Composition Of Enzymatically Active Telomerasementioning
confidence: 99%
See 1 more Smart Citation
“…Telomerase activity is negatively regulated by the nucleolar protein PIN2/TERF1-interacting telomerase inhibitor 1 (PINX1) [171]. Nucleophosmin (NPM) and microspherule protein 2 (MCRS2) may be S phase-specific co-effectors of PINX1, working against each other to modulate the human TERT pool (reviewed in [172]). Telomerase is then recruited to Cajal bodies (CBs).…”
Section: Composition Of Enzymatically Active Telomerasementioning
confidence: 99%
“…Thus, while telomerase-interacting proteins (reviewed in [172]) show relatively extensive conservation, individual interactions remain to be elucidated and carefully classified into direct and indirect ones. Due to the recently described differences in TR biogenesis pathways between plants and ciliates on one hand, and mammals and yeasts on the other hand, the orthologs of known TR interactors in humans (dyskerin, NOP10, NHP2, NAF1 or GAR1), as well as, e.g., orthologues of the La-family protein (p65) from ciliates, or Sm proteins from yeasts (reviewed in [64]), should also be examined in plants.…”
Section: Composition Of Enzymatically Active Telomerasementioning
confidence: 99%
“…In the first instance, cellular immortalization is crucial for cancer cell survival and unattainable without sustained telomere maintenance [ 8 , 9 , 10 , 11 ]. In the second instance, TERT has many proposed non-canonical extra-telomeric roles, primarily by regulating gene expression as a transcriptional factor/co-factor [ 89 ]. Of note, TERT is involved in Wnt/β-catenin [ 90 , 91 ] and Nuclear Factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we applied the latter approach and designed full-length rat TERT lacking NoLS and catalytic center (TERTin). Besides, we have recently shown that the bulk of epitopes inducing lytic T cell response in TERT DNA immunized mice is localized in its reverse transcriptase domain, aa 605-935 in human, and 595-929 in rat TERT [ 35 ] (for the domain structure, see [ 81 , 82 ]). Expression of the rtTERT domain by murine adenocarcinoma cells drastically reduced their tumorigenic and metastatic activities [ 35 ].…”
Section: Discussionmentioning
confidence: 99%